The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10646-015-1509-6
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial exposure and effects of Headline AMP® Fungicide on amphibians

Abstract: Recent studies have demonstrated that a pyraclostrobin-containing fungicide (Headline(®) Fungicide--Headline(®) Fungicide and Headline AMP(®) Fungicide are registered trademarks of BASF) is toxic to amphibians at environmentally relevant concentrations. However, these studies were performed in a laboratory setting of a worst-case direct exposure in clean media. Interception of spray by the crop canopy and ground cover used by animals for security cover will influence exposure. Thus, risk to amphibians is uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Juveniles are more likely to be present in crop fields later in the season when canopy cover is higher, which would reduce direct exposure from spray, and thus exposure to chemicals via alternate exposure routes or exposure to sublethal concentrations of chemicals may be more likely. Our results, in combination with data from Cusaac et al suggesting high rates of canopy interception in a routine corn exposure scenario, suggest that risk of Headline AMP fungicide exposure and acute effects (e.g., mortality) to terrestrial amphibians in a healthy corn system is minimal. Indeed, mortality of juvenile A. cognatus from Headline AMP fungicide may only be expected in the event of a direct overspray exposure, and there was no indication of sublethal toxicity as measured by prey orientation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Juveniles are more likely to be present in crop fields later in the season when canopy cover is higher, which would reduce direct exposure from spray, and thus exposure to chemicals via alternate exposure routes or exposure to sublethal concentrations of chemicals may be more likely. Our results, in combination with data from Cusaac et al suggesting high rates of canopy interception in a routine corn exposure scenario, suggest that risk of Headline AMP fungicide exposure and acute effects (e.g., mortality) to terrestrial amphibians in a healthy corn system is minimal. Indeed, mortality of juvenile A. cognatus from Headline AMP fungicide may only be expected in the event of a direct overspray exposure, and there was no indication of sublethal toxicity as measured by prey orientation.…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, direct exposure may result in some mortality, and because canopy cover is not ubiquitous throughout crop fields, animals could experience direct exposure to the fungicide during crop treatment. However, canopy interception reduces rates of the fungicide at ground level , and other factors likely govern exposure risk, including the activity period and habitat use by the animal . Toads may or may not be active during the daytime as a function of temperature, moisture, and other factors, all of which influence their presence in a given area .…”
Section: Discussionmentioning
confidence: 99%
“…Smalling et al [22] found 14 pesticide active ingredients and 3 pesticide metabolites in sediment samples from wetlands actively draining agricultural fields in Iowa. Interception by vegetation during the growing season may reduce pesticide exposure and related mortality among amphibians [52], indicating there is likely variation in pesticide accumulation and effects across seasons. Glyphosate is known to cause mortality in amphibians [49,50] and its mobility in soils can be affected by the presence of phosphate fertilizers [51].…”
Section: Discussionmentioning
confidence: 99%
“…The authors did indicate, however, that deleterious effects were evident only under worst‐case exposure scenarios. In a follow‐up study in which adult amphibians were placed in pesticide‐treated and untreated fields, they found that toxicity was greatly reduced, which the authors attributed to a reduction in exposure resulting, most likely, from canopy interference (Cusaac et al ). Alternatively, Brühl et al () reported relatively high toxicity to the European common frog ( Rana temporaria ), resulting from direct overspray of 7 pesticides at environmentally relevant exposure levels.…”
Section: Introductionmentioning
confidence: 99%